Dont be afraid and run away from challenges, secret of Thiew Jih Herngs success, recipient of UMP Chancellor Award - Safriza, Baharuddin (2022)
PAYA Besar, 6 August 2022 – “Do not be afraid and always welcome and do not run from challenges because you do not know what you are capable of,” said Thiew Jih Herng, 25, graduand of B.Eng (Hons.) Civil Engineering, Universiti Malaysia Pahang (UMP).